Amauroderma trichodermatum (Ganodermataceae, Basidiomycota): first record from Bolivia and geographic distribution map, with notes on nomenclature and morphology - Robledo, Gerardo Lucio (2015)
Amauroderma trichodermatum is reported from Bolivia, the collection being the fourth one known worldwide. The species is unique in the genus by having a hirsute pileus and a monomitic hyphal system. The use of the epithet “trichodermatum” as a correction for the typographical error “trichodematum” is proposed. A description and illustrations are provided based on the fresh Bolivian specimen, which has been compared with the type.